Phytoconstituents of Lantana camara L.: Rekindling Hope in the Cancer Treatment - Kathuria, Ishita; Joshi, Mit; Patel, Bhoomika M.; Dhobi, Mahaveer (Current Bioactive Compounds, 2022)
Background: Lantana camara L. belongs to the family Verbenaceae. It originated in Tropical America in Southern Georgia and the North of Texas, and was introduced in Calcutta, India, in the year 1809 as an ornamental hedge. The plant L. camara is also distributed in Southeast Asia, China, Australia, Brazil, West Indies, Kenya, Mexico, East Africa, and Tanzania. Many of its phytoconstituents possess medicinal properties which are used traditionally to treat fever, uterine hemorrhage, and excess menstrual discharge, chronic ulcers, rheumatism, gonorrhea, toothache, gastrointestinal pain, etc., and it has been used in Brazil for curing malaria, mange, headaches, colds, and fevers. Objective: The review elaborates traditional practices related to Lantana camara L., its phytochemistry, and its role in various types of cancers.. Methods: The data on L. camara were collected through different online databases, like Web of Science, PubMed, Science Direct, Springer, and Google Scholar. Results: Major phytoconstituents isolated from the plant shows anticancer activity, especially lantadene A-D, icterogenin, oleanolic acid, lantacamaric acid A, B, oleanonic acid, etc. In vitro and in vivo studies demonstrate the potential of the plant for various cancers. Certain extracts, isolated compounds, and their semi-synthetic derivatives have depicted a significant cytotoxic and anti-proliferative effect. Conclusion: Clinical studies related to the therapeutic efficacy of Lantana camara L. are not yet established, therefore, making it crucial to direct future researches in this area.
Keywords: colon cancer